STRUCTURE-PROPERTY ENGINEERING OF LOW-EMISSION STARCH-GELATIN BIO-ADHESIVES VIA POLYLACTIC ACID MODIFICATION - Agbogo, Ugbetan Victor; Abdulazeez, Ahmed; Okafor, Obiageli Evelyn; Bognet, Obed; Ike-Muonso, Nnanyelugo Martin; Joshua, Matthew; Igogo, Akpovofene Roseline; Kollere, Abubakar Shehu; Imoh, Emmanuel Obioha; Nasira, Mahmood (FUDMA Journal of Sciences, 2026)
The increasing demand for sustainable, low-emission adhesives has heightened interest in bio-derived polymer systems that can replace petroleum-based formulations without losing performance. In this study, the structure–property relationships of starch- and gelatin-based bio-adhesives were systematically engineered through modifications with polylactic acid (PLA) and polyvinyl acetate (PVAc). Adhesives were formulated using starches extracted from Ipomoea batatas, Manihot esculenta, and Eleusine coracana, combined with hide-derived gelatin, with controlled variations in modifier content. Comprehensive physicochemical characterization was performed, including measurements of viscosity, density, pH, isoelectric point, moisture and ash content, total volatile organic compounds (TVOC), and peel strength on leather substrates. The results show that incremental incorporation of PLA/PVAc (PVA) causes significant changes in rheology, molecular packing, and emission behavior, indicating polymer–polymer interactions and network restructuring within the adhesive matrix. Moderate levels of modifiers resulted in optimized viscosity, improved peel strength, and enhanced formulation stability, while excessive loading disrupted biopolymer entanglement and reduced mechanical performance. Importantly, all bio-adhesive formulations had TVOC levels well below international regulatory limits, confirming their low-emission profile. Among the systems examined, Eleusine coracana starch modified with 20% PVAc achieved peel strength comparable to a commercial adhesive standard. Overall, this work provides a mechanistic framework for designing high-performance, environmentally friendly starch–gelatin bio-adhesives and supports their potential for industrial use as sustainable alternatives to conventional synthetic adhesives.
Keywords: Bio-Based Adhesives; Starch–Gelatin Blends; Polylactic Acid Modification; Structure–Property Relationships; Low-VOC Adhesives; Physicochemical Characterization; Peel Strength; Sustainable Polymer Engineering